EVALUASI PENGGELOLAAN DANA BOS (STUDI KASUS PADA SMA BASTREN DARUL FATIHIN BADAS) - Hidayah, Dhea Evanda Mu’amarotul; Puspita, Erna; Sugeng, Sugeng (Universitas Nusantara PGRI Kediri, 2022)
School operational assistance is a government assistance program for non-personal inventory financing costs for education units.This has the purpose of evaluating usage,management, and reporting of school operational assistance funds. The research methods has used is qualitative approach. The data source is taken from primary data and secondary data. The data collection procedures using the interview method, observation, and documentation. The results of this research are (1)The use of data is not right with the technical guidelines for school operational costs in 2021, because in the use of funds for the operational costs of bastren Darul Fatihin High School there are 12 components, has financed by school operational assistance, but just 7 components can be fulfilled. (2)The management of school operational assistance funds is with the technical guidelines for operational assistance in 2021, because this management has used-with school-based management, and through the open way and must there is the headmaster as the main person in charge. (3)The management of school operational assistance funds has been right with the technical guidelines for operational assistance in 2021 to report evidence of every purchase or spending that will be made of note or receipt that has been right with RKAS that has been specified.